2016
DOI: 10.1007/s00339-016-9648-z
|View full text |Cite
|
Sign up to set email alerts
|

Photodisruption of a thin membrane near a solid boundary: an in vitro study of laser capsulotomy

Abstract: A Nd:YAG laser photodisruption is a well-established tool for intraocular surgery, such as treatment of posterior capsule opacification that affects the visual function. During the intraocular procedure, called laser capsulotomy, the excitation pulse is focused several times just behind the posterior capsule and intraocular lens to create the central opening in the opacified capsule. We built an in-vitro experiment to (i) clarify the influence of the distance between the intraocular lens and the posterior caps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…The aim of this work is to study the propulsion effects during pulsed laser ablation in liquids [13] that is important for diversity of applications, including nanoparticle generation [14,15], laserinduced forward transfer [16,17], laser shock peening [18][19][20] and different laser medical applications [21][22][23]. The propulsion effects are investigated for different shapes of a blind hole filled with different volumes of water.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this work is to study the propulsion effects during pulsed laser ablation in liquids [13] that is important for diversity of applications, including nanoparticle generation [14,15], laserinduced forward transfer [16,17], laser shock peening [18][19][20] and different laser medical applications [21][22][23]. The propulsion effects are investigated for different shapes of a blind hole filled with different volumes of water.…”
Section: Introductionmentioning
confidence: 99%
“…The description of the wave propagation and superposition is similar to the previous case, with a few differences. The source is now closer to the front of the eye, approximately in the center of the curvature of the cornea [31]. The radius of curvature of the wavefront arriving at the reflecting boundary is practically the same as the radius of curvature of the boundary itself.…”
Section: Resultsmentioning
confidence: 98%
“…In the study of laser capsulotomy by (Hawlina et al, 2016) the authors showed that in the case of a wider gap between the intraocular lens and the posterior capsule fewer laser pulses were needed to achieve the desired rupture of the capsule. This observation is consistent with the findings of this paper, where most pronounced interaction between the bubble and the membrane was observed in the case gap size which was large compared to bubble radius.…”
Section: Discussionmentioning
confidence: 99%